The structural geology of the Naukluft Nappe Complex and its relationship to the Damara Orogenic Belt, South West Africa/Namibia - Hartnady, Christopher John Hubert (Department of Geological Sciences, 2016)
The Naukluft nappe complex has been quoted as a classic example of gravity gliding tectonics (Korn & Martin, 1959). Situated close to the southern margin of the Damara orogenic belt, it provides a key to the persistent controversy over the correlation of the "geosynclinal" Damara Supergroup with the Nama Group on the Kalahari craton. It also contains critical evidence bearing on the timing and large-scale geodynamics of the Late Precambrian-Early Palaeozoic Damara orogeny, particularly the hypothesis that it involved plate tectonic processes of subduction and continental collision in the southern zones.